Notification Methods in Wireless Systems - Nawrocki, Piotr; Jakubowski, Mikołaj; Godzik, Tomasz (Computer Science, 2017)
Recently, there has been an increasing need for secure, efficient, and simplenotification methods for wireless systems. Such systems are meant to provideusers with precise tools best suited for work or leisure environments, and a lotof effort has been put into creating a multitude of applications. At the sametime, however, not much research has been made into determining which of theavailable protocols are best suited for each individual task. A number of basicnotification methods are presented here, and tests have been performed for themost-promising ones. An attempt has been made to determine which of themethods have the best throughput, latency, security, and other characteristics.A comprehensive comparison is provided, which can be used to select the rightmethod for each individual project. Finally, conclusions are provided, and theresults from all of the tests conducted are discussed.